Evaluating the impact of the EU Medical Device Regulation (MDR) on mortality and device availability in Germany - Afschin Gandjour (PLoS ONE, 2026)
Introduction The EU Medical Device Regulation (MDR), effective since May 25, 2017, aims to enhance the safety and quality of medical devices within the EU. This study models the potential net mortality implications of the MDR in Germany under explicit assumptions about safety improvements, market withdrawals, and certification delays. Methods A combined top-down and bottom-up approach was employed to evaluate the impact of the EU MDR on mortality in Germany. The top-down approach estimated avoided deaths using the Keyfitz–Vaupel life-table elasticity, while the bottom-up approach quantified mortality reductions attributable to individual MDR-regulated medical devices. Based on the results of both approaches, the analysis also estimated the number of deaths potentially resulting from market withdrawals and certification delays. Results Official German reports attribute an average of 17 device-related deaths annually, whereas international estimates suggest the true figure may reach up to 2,500 per year. Market withdrawals and certification delays associated with MDR implementation were modelled as potentially contributing an estimated 163–1,884 additional annual deaths and a one-time mortality burden of 700–4,200 deaths. Conclusion Under central assumptions, the MDR is consistent with long-term reductions in device-related mortality, but transition-period certification bottlenecks and withdrawals—especially for niche/pediatric devices—can offset gains in the short to medium term. Targeted mitigation is warranted to secure benefits and limit unintended harms.